Effect of alprostadil combined with beraprost sodium tablet sequential therapy in early mutation and long term survival of arteriovenous fistula - YU Chong; YAN Jian-jun; YU Yang; HE Fan; Xiong Wen-fang; LIU Wei (Linchuang shenzangbing zazhi)
Objective To observe the effect of alprostadil combined with beraprost sodium tablet sequential therapy in early mutation and long term survival of arteriovenous fistula(AVF).Methods Weretrospectively analyzed 312 uraemia patients who received AVF operation first time between January 2013 and March 2014.All patients were given radialartery-cephalic vein standard fistulation.Forty-six patients were administered alprostadil(20 μg i.v.drip for 3 days in hospital) combined with beraprost sodium tablet(20 μg P.O.for 3 months for outpatient) sequential therapy as study group.Forty-six patients without treatment of alprostadil or beraprost sodium were included into control group.These two groups had the same clinical materials,such as age,the diameter of artery and vein before operation,primary disease constitution rate.The fistula dysfunctional rate in 1 year,fistula mutation time,average fistula flow volume and arterial end diastolic velocity 1 year postoperation were assessed.Results In study and control groups,the fistula dysfunctional rate was 10.9%and28.2%respectively(P=0.035 5),the mean maturation time was(42.1±6.5)and(55.5±5.8) days respectively(P<0.001),the mean blood flow was(789 ± 101) and(556 ± 132) mL/min respectively(P<0.001),and the arterial end diastolic velocity was(151.5 ± 14.5) and(113 ± 20.1) cm/s respectively(P<0.001).Conclusions Our data indicated that the sequential therapy of alprostadil combined with beraprost sodium tablet is effective and safe for the prevention of primary AVF failure in hemodialysis patients and early fistula dysfunction.